The interaction between dietary fatty acids and inflammation on insulin sensitivity - McMonagle, Jolene (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2008)
The metabolic syndrome (MetS) has been defined as a multi-component disorder consisting of a combination of metabolic abnormalities associated with an increased risk of developing type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). These metabolic disorders include glucose intolerance, hyperinsulinemia, dyslipidemia and hypertension. Recent research has demonstrated that the MetS may also be characterised by elevated inflammatory levels, endothelial dysfunction hypercoagulability and oxidative stress. An effective approach to alleviating the prevalence of the MetS may be to focus on the importance of dietary therapy, in particular the quality rather than the quantity of dietary fats being consumed. Early epidemiological studies suggest that saturated fatty acids (SFA) induces insulin resistance (IR) by altering insulin signalling, whereas, intake of monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUPA) can reverse this effect. The objective of this thesis was to investigate the association between dietary fatty acids and inflammation on insulin sensitivity and the possible involvement in attenuating other risk factors in CVD.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin